2006
DOI: 10.1074/jbc.m507602200
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Smooth Muscle Caldesmon-Tropomyosin Inhibition of the Elementary Steps of the Actomyosin ATPase

Abstract: Caldesmon is a component of smooth muscle thin filaments that inhibits the actomyosin ATPase via its interaction with actin-tropomyosin. We have performed a comprehensive transient kinetic characterization of the actomyosin ATPase in the presence of smooth muscle caldesmon and tropomyosin. At physiological ratios of caldesmon to actin (1 caldesmon/7 actin monomers) actomyosin ATPase is inhibited by about 75%. Inhibitory caldesmon concentrations had little effect upon the rate of S1 binding to actin, actin-S1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…126 On the other hand, it was argued that the reduced binding rate could be balanced out by a change in the dissociation rate, yielding a moderate (9%) overall maximum rate reduction that fails to account for the observed level of inhibition (75%) of the ATPase unless a higher concentration of CaD was used. 128 The discrepancy is difficult to reconcile, not only because of the subtle differences in the experimental conditions (such as ionic strength and temperature), but also due to the intrinsically complicated nature of the system that involves multiple, mutually interacting, protein species. However, it might be worthwhile to point out that the cellular contents of CaD and actin only give an averaged ratio between the two.…”
Section: Biochemical Properties and Regulatory Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…126 On the other hand, it was argued that the reduced binding rate could be balanced out by a change in the dissociation rate, yielding a moderate (9%) overall maximum rate reduction that fails to account for the observed level of inhibition (75%) of the ATPase unless a higher concentration of CaD was used. 128 The discrepancy is difficult to reconcile, not only because of the subtle differences in the experimental conditions (such as ionic strength and temperature), but also due to the intrinsically complicated nature of the system that involves multiple, mutually interacting, protein species. However, it might be worthwhile to point out that the cellular contents of CaD and actin only give an averaged ratio between the two.…”
Section: Biochemical Properties and Regulatory Functionsmentioning
confidence: 99%
“…This CooperativeAllosteric Model is supported by both structural 107 and biochemical data. 127,128 Two important pieces of evidence are that at low ratios (1:14) to actin, CaD was able to compete with not only weak, but also strong, myosin binding to actin 131 and that CaD was able to decrease the population of moving filaments without much changing the velocity in the in vitro motility assay. 132 These observations are indeed difficult to explain by the pure Competition Model.…”
Section: Biochemical Properties and Regulatory Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For experiments using low actin concentrations (below 4 M) actin was stabilized with phalloidin and used within 20 min of actin sample preparation (28). S1 was treated with N-ethyl maleimide as described by Swartz and Moss (33), and sheep aorta caldesmon was labeled with […”
Section: Methodsmentioning
confidence: 99%
“…These findings are compatible with the proposed mechanism. More recently we have investigated thoroughly the effect of caldesmon on the elementary steps of the actomyosin ATPase (28). We found that caldesmon had very little effect on the rate of S1 binding to actin-tropomyosin, acto-S1 dissociation by ATP and the rate of ADP release.…”
mentioning
confidence: 99%